A sweet spot for macrophages: Focusing on polarization. (May 2021) - Yang, Depeng; Yang, Lijun; Cai, Jialing; Hu, Xibo; Li, Huaxin; Zhang, Xiaoqing; Zhang, Xiaohan; Chen, Xinghe; Dong, Haiyang; Nie, Huan; Li, Yu
Abstract: Macrophages are a type of functionally plastic cells that can create a pro-/anti-inflammatory microenvironment for organs by producing different kinds of cytokines, chemokines, and growth factors to regulate immunity and inflammatory responses. In addition, they can also be induced to adopt different phenotypes in response to extracellular and intracellular signals, a process defined as M1/M2 polarization. Growing evidence indicates that glycobiology is closely associated with this polarization process. In this research, we review studies of the roles of glycosylation, glucose metabolism, and key lectins in the regulation of macrophages function and polarization to provide a new perspective for immunotherapies for multiple diseases. Graphical Abstract: Schematic representation of glycosylation, glucose metabolism and lectins associated with macrophages polarization. The polarization phenotypes of macrophages are dramatically influenced by alterations of glycosylation, glucose metabolism and lectins. On account that nearly all functional membrane proteins on the surface of macrophages are glycosylated, various glycosylation modifications such as O -GlcNAylation, N -glycosylation and sialylation can significantly affect their active state and functional characteristics. O -GlcNAylation and N -glycosylation exhibit a relatively complicated effects on macrophages polarization mainly through regulating NF-κB pathway. In details, they can activate NF-κB pathways in some disease models so as to induce macrophages into the pro-inflammatory M1 phenotype while in others, they may possibly inhibit NF-κB pathways to induce macrophages into anti-inflammatory M2 phenotype. By comparison, the influence of sialylation on macrophages polarization seems more simple that it can enhance macrophages' tolerance to LPS and primarily induce them into M2 phenotype. Glucose metabolism can provide energy and substrates for glycosylation process, which also contributes to the transition between M1 and M2 type macrophages. The strengthen of glycolysis as well as PPP can induce macrophages into M1 phenotype while enhancement of HBP as well as TCA cycle can induce them into M2 macrophages. Lectins, which can specifically recognize glycans, also contribute to macrophages polarization. Siglec-E，Dectin-1 and Mincle can induce macrophages into M1 phenotype while Siglec-9，Siglec-15 and CD206 can induce macrophages into M2 phenotype. ga1 Highlights: This review focuses on the effects of glycobiology for macrophage polarization. This review explores the consequences of glycosylation, glucose metabolism and lectins in macrophage polarization. This review proposes new potential immunotherapies targeting for macrophages in the future.